Seasonal changes in prescribing of long-acting beta-2-agonists-containing drugs. Issue 7 (July 2015) - Rottenkolber, M.; Voogd, E.; van Dijk, L.; Primatesta, P.; Becker, C.; de Groot, M.C.H.; Plana, E.; Alvarez, Y.; Durand, J.; Slattery, J.; Afonso, A.; Requena, G.; et al.
Summary Background For patients with asthma, COPD, or asthma-COPD overlap syndrome (ACOS), inter-country comparisons of seasonal changes in drug prescriptions are scarce or missing. Hence, we aimed to compare seasonal changes in prescription rates of long-acting beta-2-agonist (LABA) in four European countries. Methods A common study protocol was applied to six health care databases (Germany, Spain, the Netherlands (2), and the UK (2)) to calculate age- and sex-standardized point prevalence rates (PPRs) of LABA-containing prescriptions by the 1st of March, June, September, and December of each year during the study period 2002–2009. Seasonal variation of PPRs was quantified using seasonal indexes (SIs; based on the ratio-to-moving-average-method) and SIs averaged over the study period (aSI) stratified by sex, age, and indication (asthma, COPD, or ACOS). Results There was a moderate seasonal change in LABA-containing prescriptions which was more pronounced in asthma or COPD patients compared to ACOS patients. For asthma and ACOS patients, highest seasonal variation was found for patients living in Spain (aSI: 87.3–110.7, aSI: 93.2–103.1) whereas for COPD highest seasonal variation was revealed for the NPCRD database (the Netherlands) (aSI: 92.2–105.6). Regarding age and sex, highest seasonal variation was found in Spanish boys under 10 years of age having a diagnosis of asthma. Conclusions By applying a common analysis in six databases, we could observe moderate overall seasonal changes in LABA-containing prescription rates in patients with asthma, COPD, or ACOS.